The music of time : poetry in the twentieth century - Burnside, John, 1955- (Princeton University Press, 2020)
Poetry helps us to make sense of our world, transforming what the Russian poet Osip Mandelstam called the "noise of time" into a kind of music. The Music of Time is a unique history of twentieth-century poetry by one of today's most acclaimed poets, blending incandescent personal meditations with rare insights about a broad range of poets who distilled the essence of the moment, gave voice to our griefs and joys, and shaped our collective memory. Bringing together poets from times and places as diverse as Tsarist Russia, 1960s Harlem, and Ireland at the height of the Troubles, Burnside reveals how poetry responded to the dramatic events of the century while shaping our impressions of them. He takes readers from the trenches of World War I to a prison cell in Nazi Germany, and from Rilke's grave in the Swiss Alps to Dylan Thomas's Welsh seaside. His luminous narrative is woven through with insights into the poet's creative process as well as lyrical and thought-provoking digressions on topics ranging from marriage to the Kennedy assassination. A spellbinding work of literary history, The Music of Time reveals how poets engaged with the most important issues and events of the twentieth century, and bears personal witness to the beauty and power of an art form unlike any other.